Research design and methods a process approach - Bordens, Kenneth S.; Abbott, Bruce B. (New York McGraw-Hill, 2011)
Guides students through the research process, from conceiving of and developing a research idea, to designing and conducting a study, to analyzing and reporting data. This title presents students with information on the numerous decisions they must make when designing and conducting research.
Explaining behavior -- Developing and evaluating theories of behavior -- Getting ideas for research -- Choosing a research design -- Making systematic observations -- Choosing and using research subjects -- Understanding ethical issues in the research process -- Using nonexperimental research -- Using survey research -- Using between-subjects and within-subjects experimental designs -- Using specialized research designs -- Using single-subject designs -- Describing data -- Using inferential statistics -- Using Multivariate design and analysis -- Reporting your research results.
Cover title: A process approach : research design and methods.
Keywords: Psychology -- Research -- Textbooks; Psychology -- Research -- Methodology -- Textbooks